Comprendemos textos narrativos - Cruz Lizana, Eudulia (2018)
The present proyetc learning session aims to develop spatial thinking in children, various geometry skill related and spatial reasoning are important early learning mathematic elements, but are often overlooked, because early childhood teachers does not recognize spatial thinking in children's play and they miss opportunities to develop and expand children's thinking. The first chapter is intended for the Learning planning Session. On second chapter, the basics in the Communication Area are exposed, according to the Basic Education National Curriculum (CNEB); Theoretical Support takes into account the development of mathematical competencies in children from initial level. On third chapter, Pedagogical Support is presented referring to psychopedagogical principles, pedagogical processes that are developed in a learning session. Finally, it is sought that the primary children level develop the basic competences to successfully consolidate a progressive process in their transcendental learning area like this.